2017
DOI: 10.1111/jop.12573
|View full text |Cite
|
Sign up to set email alerts
|

Current update on the diagnosis and management of head and neck hard tissue sarcomas

Abstract: Head and neck hard tissue sarcomas form a rare group of mesenchymal-derived tumours that comprise less than 1% of all head and neck neoplasms. Hard tissue sarcomas account for 20% of head and neck sarcomas and they form a heterogeneous group with a diverse origin. Unlike head and neck soft-tissue sarcomas, they have lower recurrence and mortality rates. In this study, we review the current management of head and neck hard tissue sarcomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 73 publications
0
18
0
Order By: Relevance
“…Previous studies that included a larger cohort of 12,755 patients mentioned that further data accumulation for predictors of HNS due to rare tumors and various histological subtypes is needed [1][2][3]. Indeed, Ketabachi et al had reported that the surgical margin was a survival predictor for 25 patients with HNS [7].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies that included a larger cohort of 12,755 patients mentioned that further data accumulation for predictors of HNS due to rare tumors and various histological subtypes is needed [1][2][3]. Indeed, Ketabachi et al had reported that the surgical margin was a survival predictor for 25 patients with HNS [7].…”
Section: Discussionmentioning
confidence: 99%
“…HNSs have been divided into those of the bone and those of the soft tissue [1,2]. Although the TNM staging system has been broadly accepted as a useful predictor for various malignant tumors, there remains a lack of clari cation for soft tissue sarcomas of the head and neck in the staging system outlined in the eighth edition of the UICC TNM classi cation [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, surgical intervention with wide excision of the neoplasm and the achievement of clear margins is generally paramount in the treatment of adult patients with head and neck sarcoma . In the case of high‐grade sarcomas, when surgical intervention with a wide excision is not possible or when facing unclear margins after surgical intervention, adjuvant therapeutic intervention in terms of RT, chemotherapy, or a combination should be recommended . The radiosensitivity and chemosensitivity are, however, highly dependent upon the histologic subtype and the patient's age .…”
Section: Discussionmentioning
confidence: 99%
“…In the case of high‐grade sarcomas, when surgical intervention with a wide excision is not possible or when facing unclear margins after surgical intervention, adjuvant therapeutic intervention in terms of RT, chemotherapy, or a combination should be recommended . The radiosensitivity and chemosensitivity are, however, highly dependent upon the histologic subtype and the patient's age . Importantly, microscopically incomplete tumor resection has been shown to reduce OS and local control of sinonasal soft tissue sarcomas .…”
Section: Discussionmentioning
confidence: 99%